The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1590/s0103-84782005000500031
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros bromatológicos e fermentativos das silagens de milho e girassol

Abstract: RESUMO Foi desenvolvido no Instituto de Zootecnia, Agência Paulista de Tecnologia dos Agronegócios (APTA), São Paulo um experimento com o objetivo de avaliar quimicamente a qualidade das silagens e a degradação ruminal da matéria seca (MS), fibra detergente neutra (FDN) e proteína bruta (PB) das

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 3 publications
3
14
1
18
Order By: Relevance
“…The values found for CP in the present study were close to those reported by Vilela (1985), who obtained contents of 4 to 7% in the DM, although inferior to those mentioned by Evangelista et al (1991) and Obeid et al (1992), who obtained contents of 6.9 to 7.1 and from 5.9 to 10.9 in the DM, respectively, for the silage of corn intercropped with soybean, and Possenti et al (2005), who found mean values of 9.4% CP in the corn silage.…”
Section: Resultssupporting
confidence: 85%
“…The values found for CP in the present study were close to those reported by Vilela (1985), who obtained contents of 4 to 7% in the DM, although inferior to those mentioned by Evangelista et al (1991) and Obeid et al (1992), who obtained contents of 6.9 to 7.1 and from 5.9 to 10.9 in the DM, respectively, for the silage of corn intercropped with soybean, and Possenti et al (2005), who found mean values of 9.4% CP in the corn silage.…”
Section: Resultssupporting
confidence: 85%
“…Agrotec., Lavras, v.38, n.5, p.497-505, set./out., 2014 Corn silage CP average was lower (7.3%) than that of sunflower silage (9.3%) and there was no interaction effect between silage sources and glycerol levels. Possenti et al (2005) and Paziani et al (2009) found values between 6.7 to 9.4% CP for corn silage and Viana et al (2012) values between 11.6 and 12.1% for sunflower silage. The lower results for sunflower silage CP may be related to the variety and the vegetative stage of the plant at the time of cutting.…”
Section: Parametermentioning
confidence: 95%
“…Similarly, the corn silage NDF and ADF decreased with the addition of glycerol. Possenti et al (2005) evaluating the chemical composition of corn silages found levels of 63, 32 and 62 of %NDF, ADF and TDN, respectively. In the present study, the addition of 45% glycerol in corn silage provided NDF and ADF means of 25.3% and 4.3%, respectively, and for the NDT, levels of 88%.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…: 45.20%+8.54%) of potentially absorbed forage. For the purpose of comparison, 57.2% and 67.7% of sunflower and corn silage, respectively, is expected to be absorbed by ruminants (POSSENTI et al, 2005).…”
Section: Resultsmentioning
confidence: 99%